Coactosin Promotes F-Actin Protrusion in Growth Cones Under Cofilin-Related Signaling Pathway - Hou, Xubin; Nozumi, Motohiro; Nakamura, Harukazu; Igarashi, Michihiro; Sugiyama, Sayaka (Frontiers in Cell and Developmental Biology, 2021)
During brain development, axon outgrowth and its subsequent pathfinding are reliant on a highly motile growth cone located at the tip of the axon. Actin polymerization that is regulated by actin-depolymerizing factors homology (ADF-H) domain-containing family drives the formation of lamellipodia and filopodia at the leading edge of growth cones for axon guidance. However, the precise localization and function of ADF-H domain-containing proteins involved in axon extension and retraction remain unclear. We have previously shown that transcripts and proteins of coactosin-like protein 1 (COTL1), an ADF-H domain-containing protein, are observed in neurites and axons in chick embryos. Coactosin overexpression analysis revealed that this protein was localized to axonal growth cones and involved in axon extension in the midbrain. We further examined the specific distribution of coactosin and cofilin within the growth cone using superresolution microscopy, structured illumination microscopy (SIM), which overcomes the optical diffraction limitation and is suitable to the analysis of cellular dynamic movements. We found that coactosin was tightly associated with F-actin bundles at the growth cones and that coactosin overexpression promoted the expansion of lamellipodia and extension of growth cones. Coactosin knockdown in oculomotor neurons resulted in an increase in the levels of the inactive, phosphorylated form of cofilin and dysregulation of actin polymerization and axonal elongation, which suggests that coactosin promoted axonal growth in a cofilin-dependent manner. Indeed, the application of a dominant-negative form of LIMK1, a downstream effector of GTPases, reversed the effect of coactosin knockdown on axonal growth by enhancing cofilin activity. Combined, our results indicate that coactosin functions promote the assembly of protrusive actin filament arrays at the leading edge for growth cone motility.